2018
DOI: 10.1525/collabra.168
|View full text |Cite
|
Sign up to set email alerts
|

Looking on the Bright Side: Replicating the Association between Brightness and Positivity

Abstract: The present study is a pre-registered replication of a study by Specker et al. (2018) that tests the hypothesis that brightness of colors is associated with positivity. Our results showed an implicit association between brightness and positivity in both Study 1 and Study 2, however, an explicit association between brightness and positivity was only found in Study 2, thereby replicating 3 out of 4 effects. To investigate these effects in more detail, we present a meta-analysis of both the original and the repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…hue, brightness, and saturation) and perceived warmth or weight [40][41][42][43]. Research has also shown a connection between brightness of colors and positivity [22,[44][45][46][47][48], which could speculatively contribute to explaining the happy-sad finding. However, we also included a negative-positive scale as such.…”
Section: Plos Onementioning
confidence: 99%
“…hue, brightness, and saturation) and perceived warmth or weight [40][41][42][43]. Research has also shown a connection between brightness of colors and positivity [22,[44][45][46][47][48], which could speculatively contribute to explaining the happy-sad finding. However, we also included a negative-positive scale as such.…”
Section: Plos Onementioning
confidence: 99%
“…For Liking ratings, Luminance was the strongest single predictor. This finding seems somewhat counterintuitive considering that there is a strong association between chromatic brightness and positivity (Specker & Leder, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The instrument assesses six formal-perceptual (depth, stroke, balance, complexity, color saturation, and temperature) and six conceptual-representational (realism, emotion, animacy, abstraction, symbolism, and objective accuracy) attributes of paintings. Some properties, such as brightness (color saturation), may be commonly experienced as positive (Specker, Leder, & Zwaan, 2018;. Other properties, such as warmth (color temperature) and happiness (affect), may be person-and artwork-specific (Specker et al, 2020a).…”
Section: Engagementmentioning
confidence: 99%
“…Modeling aesthetic cognitivism is not straightforward. Although some properties of artworks may have universal effects on people (e.g., brightness and positivity; Specker, Leder, Zwaan, 2018;, artworks themselves are unlikely to be processed in the same way by everyone-people differ in their preferences for artworks (Chatterjee & Vartanian, 2016;Fayn et al, 2019). Researchers therefore need to provide different artworks to encourage engagement for different people.…”
Section: Aesthetic Cognitivism Review 25mentioning
confidence: 99%